Multicentre study evaluating the surgical learning curve for posterior retroperitoneoscopic adrenalectomy. Issue 5 (1st March 2018) - Vrielink, O. M.; Engelsman, A. F.; Hemmer, P. H. J.; de Vries, J.; Vorselaars, W. M. C. M.; Vriens, M. R.; Karakatsanis, A.; Hellman, P.; Sywak, M. S.; van Leeuwen, B. L.; El Moumni, M.; Kruijff, S.
Abstract : Background: Posterior retroperitoneoscopic adrenalectomy has gained international popularity in the past decade. Despite major advantages, including shorter duration of operation, minimal blood loss and decreased postoperative pain, many surgeons still prefer laparoscopic transperitoneal adrenalectomy. It is likely that the unfamiliar anatomical environment, smaller working space and long learning curve impede implementation. The present study assessed the number of procedures required to fulfil the surgical learning curve for posterior retroperitoneoscopic adrenalectomy. Methods: The first consecutive posterior retroperitoneoscopic adrenalectomies performed by four surgical teams from university centres in three different countries were analysed. The primary outcome measure was duration of operation. Secondary outcomes were conversion to an open or laparoscopic transperitoneal approach, complications and recovery time. The learning curve cumulative sum (LC‐CUSUM) was used to assess the learning curves for each surgical team. Results: A total of 181 surgical procedures performed by four surgical teams were analysed. The median age of the patients was 57 (range 15–84) years and 61·3 per cent were female. Median tumour size was 25 (range 4–85) mm. There were no significant differences in patient characteristics and tumour size between the teams. The median duration of operation was 89 (range 29–265) min. There were 35 perioperative and postoperative complications among the 181 patients (18·8 per cent); 17 of 27 postoperative complications were grade 1. A total of nine conversions to open procedures (5·0 per cent) were observed. The LC‐CUSUM analysis showed that competency was achieved after a range of 24–42 procedures. Conclusion: In specialized endocrine surgical centres between 24 and 42 procedures are required to fulfil the entire surgical learning curve for the posterior retroperitoneoscopic adrenalectomy. Abstract : Large annual case‐load required